North Atlantic Gateway: Test bed of deep‐sea macroecological patterns. (7th June 2019) - Jöst, Anna B.; Yasuhara, Moriaki; Wei, Chih‐Lin; Okahashi, Hisayo; Ostmann, Alexandra; Martínez Arbizu, Pedro; Mamo, Briony; Svavarsson, Jörundur; Brix, Saskia
Abstract: Aim: The deep waters around Iceland, known as the North Atlantic Gateway, constitute an ideal location to investigate deep‐sea ecological hypotheses. We constructed a comprehensive deep‐sea macroecological dataset of the North Atlantic Gateway region and investigated the controlling factors of large‐scale, deep‐sea species diversity patterns. Location: Sub‐polar North Atlantic Ocean. Time period: Modern. Major taxa studied: Ostracoda (Crustacea). Methods: We investigated deep‐sea biodiversity patterns and applied ecological modelling (multiple regression and model averaging) to test whether these patterns are governed by environmental factors such as temperature, surface primary productivity, and seasonality. Beta diversity analyses were applied to evaluate the effect of a geographical barrier (Greenland‐Iceland‐Faeroe Ridge) on deep‐sea benthic faunal distributions. Results: We constructed a deep‐sea macroecological dataset with 32 stations, 5, 676 specimens, and >122 species. We confirmed a linear latitudinal diversity gradient with higher diversity in the North Atlantic proper than in the Nordic Seas. We report a unimodal depth diversity gradient south of the ridge, but a linear diversity‐decline with depth north of the ridge. The turnover component of beta diversity increased towards the ridge. Main conclusions: We found both temperature and surface primary production are important for deep‐sea biodiversity. For the first time, we report a significant diversity‐temperature relationship in both macroecological (spatial; this study) and existing paleoecological (time‐series) data for the same taxa. In addition to temperature and surface primary production, bathymetric features such as a shallow ridge acting as a barrier are an important factor for deep‐sea biodiversity distribution. The low diversity of the Nordic Seas is likely due to a combination of low temperatures and bathymetric barriers. These results substantially expand our understanding of the well‐known yet poorly understood Greenland‐Iceland‐Faeroe Ridge faunal transition with possible insight to its cause.